(untitled) (The International Journal for Scientific Research, 2024)
The study aimed to identify interactive multimedia, understand the reality of using interactive multimedia in teaching digital technology from the perspective of secondary school digital technology teachers, and uncover the challenges of using interactive multimedia in teaching digital technology from the perspective of secondary school digital technology teachers. The study used a descriptive approach according to the nature and objectives of the research. The reality of using interactive multimedia in teaching digital technology for secondary school was studied. The research sample consisted of 156 teachers of digital technology for secondary school under the supervision of the Education Administration in Al-Madinah Al-Munawwarah. A questionnaire tool was used to measure the reality of using interactive multimedia. The study found that the frequencies, percentages, means, and standard deviations regarding the reality of using interactive multimedia in teaching digital technology from the teachers’ perspective ranged from (4.12) to (0.88). The results of this study indicate that teachers emphasized the importance of these skills and the necessity of dealing with interactive multimedia. The reality of their use of interactive multimedia is considered limited and does not achieve the desired goals. The study sample also pointed out the challenges associated with the use of interactive multimedia, such as technical, human, and material challenges.